Recent Advances in Information Systems and Technologies Volume 1 - Rocha, Álvaro; Correia, Ana Maria; Adeli, Hojjat; Reis, Luís Paulo; Costanzo, Sandra; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book presents a selection of papers from the 2017 World Conference on Information Systems and Technologies (WorldCIST'17), held between the 11st and 13th of April 2017 at Porto Santo Island, Madeira, Portugal. WorldCIST is a global forum for researchers and practitioners to present and discuss recent results and innovations, current trends, professional experiences and challenges involved in modern Information Systems and Technologies research, together with technological developments and applications. The main topics covered are: Information and Knowledge Management; Organizational Models and Information Systems; Software and Systems Modeling; Software Systems, Architectures, Applications and Tools; Multimedia Systems and Applications; Computer Networks, Mobility and Pervasive Systems; Intelligent and Decision Support Systems; Big Data Analytics and Applications; Human-Computer Interaction; Ethics, Computers & Security; Health Informatics; Information Technologies in Education; and Information Technologies in Radiocommunications. .
System Dynamics Modeling for the Complexity of Knowledge Creation within Adaptive Large Programs Management -- The Rio de Janeiro, Brazil, experience using digital initiatives for the co-production of the public good: The case of the Operations Centre -- Data base processing programs with using extended base semantic hypergraph -- Assessment of academic digital platform through social networks in Economics degree -- Analysis for Software Process Improvement: A Systematic Literature Review -- Analysis of Data Science Tools for Sensor-Based Assessment of Quality of Life in Health Care -- Collaborative Process Mapping to Improve Work Instructions and Standardized Work -- Who can assess Human Resources performance in IT/IS projects: a review -- Analysing Functional Paradigm Concepts: The JavaScript Case -- Stochastic Petri Nets with Changeable Layout -- Analysing Functional Paradigm Concepts: The JavaScript Case -- Simple Network Management Protocol for Remote Telemetry Systems in Urban Environments -- User Modeling Framework for Context-Aware Recommender Systems -- Baby steps into an E-Health: Internet of Things in a doctor's office -- Learning Core Concepts of Business Information Systems Engineering by Teaching - Lessons Learned from a Comparative Teaching Experiment.
Keywords: Computational intelligence; Artificial intelligence; Computational Intelligence; Artificial Intelligence